ANALISIS EFISIENSI PENGGUNAAN TEMPAT TIDUR DI RSJ PROF. DR. M. ILDREM MEDAN PER RUANGAN BERDASARKAN INDIKATOR RAWAT INAP DI TRIWULAN 1 TAHUN 2018 - Siti Permata Sari Lubis; Corah Astuti (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2019)
Inpatient services may have an effect on the level of efficiency in the hospital which is wrong in the inpatient indicator that is BOR, ALOS, TOI, and BTO that have not comply with MOH standard. To analyze the wealth of using the bedroom at RSJ PROF. DR. ILDREM MEDAN. This type of research is descriptive with retrospective approach. Document study instrument review guide (daily census of inpatient in the journal). The results showed that the value of BOR, ALOS, TOI, and BTO was high enough to exceed the ideal rate according to Manistry of Health, highest BOR in Bukit Barisan with BOR value 98%, lowest BOR in D Sanggul room with 86.8%, TOI highest in room and Mawar room with value 14,76%, lowest TOI value in room D Sanggul with value 1,13%. The conclusions used by many outdoor beds in accordance with the Manistry of Health were given the results of the overall BOR room 91.18 according to the Manistry of health Standard 60-85%. ALOS value 86.125 whereas According to Ministry of Health Standard 6- 9 days, BTO Value 14.7 on According to Ministry of Health Standard 40-50 times and value of TOI 8.99 According to Standard Depkes 1-3 days. Divide To the officer to improve the quality of service to patient.